Exploring the phylogenetic diversity and antimicrobial activity of non-aureus staphylococci and mammaliicocci isolated from teat apices of organic dairy cows - Peña-Mosca, F.; Gaire, T. N.; Dean, C.; Ferm, P.; Manriquez, D.; Pinedo, P.; Noyes, N.; Caixeta, L. (Frontiers in Microbiology, 2025)
Prior studies have suggested that non-aureus staphylococci and mammaliicocci (NASM) possess inhibitory activity against mastitis pathogens. However, their impact on udder health outcomes and the mechanisms underlying this potential protective effect remain poorly understood. Our first objective was to identify NASM species on teat apices of organic dairy cows, assess their within-species phylogeny, and explore associations with presence of intramammary infections (IMI) and genomic features, including antimicrobial peptides (AMPs), virulence, and resistance genes. The second objective was to evaluate the in vitro antimicrobial activity of NASM isolates against mastitis pathogens and examine its associations with taxonomy, phylogeny, AMP genes, and IMI. Milk and teat apex swabs were collected weekly from 114 cows on two organic farms. Milk was cultured to identify Staphylococcus aureus (SAU) or Streptococcus spp. and Streptococcus-like organisms (SSLO) IMI. A case-control study was designed to include cows with and without SAU or SSLO IMI. For each selected cow, the teat apex gauze swab collected during the week preceding IMI diagnosis (or corresponding time for controls) was aerobically cultured, and the taxonomy of isolates was determined using mass spectrometry. Isolates classified as NASM were subjected to whole genome sequencing using Illumina MiSeq. The inhibitory activity of NASM isolates was tested against SAU and Streptococcus uberis. Phylogenetic trees were constructed using Snippy and IQ-TREE. Genomes were assembled and annotated to identify species, AMP genes, virulence, and antimicrobial resistance markers. The in vitro antimicrobial activity of NASM varied across species and between cows with and without an IMI. Staphylococcus succinus was the species most frequently associated with highly inhibitory isolates, which were more prevalent in cows without IMI (19.4% vs. 5.8%). Organic dairy cow teat apices harbored multiple NASM species and strains. All isolates had at least 1 AMP associated gene in their genome. In vitro antimicrobial activity was generally unrelated to clade membership, except for isolates classified as Staphylococcus succinus. Staphylococcus aureus had high virulence gene prevalence, while NASM species showed lower, species-specific prevalence. This study advances understanding of NASM antimicrobial activity and virulence potential.